Religious Moderation By Organization Of Islamic Al-Jam’iyatul Washliyah (Character, Identity, And Attitude) - Damanik, Deniansyah; Meidina, Ahmad Rezy; Adlinnas, Ridlo; Azizah, Shofie Nurul (Islamadina : Jurnal Pemikiran Islam, 2023)
This study discusses religious moderation by the Islamic organization Al-Jam’iyhatul Washliyah (Al Washiliyah). Al Washliyah is a moderate organization; even Al Washliyah was born due to mediate (connect) between the old and young people fighting over furu’iyah (worship) issues at that time in North Sumatra. Various writings have produced that Al Washliyah is a moderate and not extreme organization. However, the forms (character) of Al Washliyah’s moderation have yet to be classified (generalized) much. This research is library research. This article found the character of Al Washliyah’s religious moderation, namely: al-Manhaj Washatiyyah (moderate manhaj), Dirasah Washatiyyah (moderate education), al-Fikr Washatiyyah (moderate thoughts/perspectives), tawazzun washatiyyah (moderate balance), mas’uliyyah diniyyah (religious responsibility) and mas’uliyyah wathaniyyah (national responsibility).